Cross-view human action recognition from depth maps using spectral graph sequences - Kerola, Tommi; Inoue, Nakamasa; Shinoda, Koichi (Computer vision and image understanding, 2017)
•A graph-based method for 3D view-invariant human action recognition is proposed.•An action is represented as a sequence of graphs.•The vertices can either be tracked skeleton joints or spatio-temporal keypoints.•A spectral graph wavelet transform is leveraged to extract features from the graphs.•The method is useful for both single- and multi-view action recognition tasks. [Display omitted] We present a method for view-invariant action recognition from depth cameras based on graph signal processing techniques. Our framework leverages a novel graph representation of an action as a temporal sequence of graphs, onto which we apply a spectral graph wavelet transform for creating our feature descriptor. We evaluate two view-invariant graph types: skeleton-based and keypoint-based. The skeleton-based descriptor captures the spatial pose of the subject, whereas the keypoint-based is able to capture complementary information about human-object interaction and the shape of the point cloud. We investigate the effectiveness of our method by experiments on five publicly available datasets. By the graph structure, our method captures the temporal interaction between depth map interest points and achieves a 19.8% increase in performance compared to state-of-the-art results for cross-view action recognition, and competing results for frontal-view action recognition and human-object interaction. Namely, our method results in 90.8% accuracy on the cross-view N-UCLA Multiview Action3D dataset and 91.4% accuracy on the challenging MSRAction3D dataset in the cross-subject setting. For human-object interaction, our method achieves 72.3% accuracy on the Online RGBD Action dataset.We also achieve 96.0% and 98.8% accuracy on the MSRActionPairs3D and UCF-Kinect datasets, respectively.